A stepwise refinement-based development of self-organising multi-agent systems: application to the foraging ants. (2016) - Graja, Zeineb; Migeon, Frédéric; Maurel, Christine; Gleizes, Marie-Pierre; Kacem, Ahmed Hadj
This paper proposes a formal modelling for self-organising multi-agent systems (SOMAS) based on stepwise refinements, with the Event-B language and the temporal logic of actions (TLA). This modelling allows to develop this kind of systems in a more structured manner. In addition, it enables to reason, in a rigorous way, about the correctness of the derived models both at the local level and the global level. Our work is illustrated by the foraging ants case study.